Die Seelsorge in Polen vor und nach der Wende - Biel, Robert J. (European Journal of Mental Health, 2012)
Pastoral Counselling in Poland before and after the Political Change: Pastoral counselling has long been widely acknowledged as a basic notion in pastoral theology. Besides caritas and revelation, it is also one of the essential issues in Church. Pastoral counselling became especially relevant during the oppression of Churches in totalitarian regimes, as in Poland after World War II. Communist authorities showed hostility towards the Church; therefore, the establishment of the Communist rule severely affected both the activity of the Polish Church and pastoral counselling. As a result, the pastoral counselling activity of the Church in Communist Poland was confined to the sacristies, so to say. This mode of Church existence was the only tolerated way of answering the spiritual needs of religious citizens but it led to a minimalistic interpretation of pastoral counselling in many places. Communism cast its shadow over the counselling activity, which struggled with a lot of difficulties especially when it was carried out in the army or prisons. This situation forced the Church to develop new forms of pastoral work in the totalitarian regime. Since freedom was regained, the Church has been facing new challenges, which are not easy to overcome. The present era calls for a paradigmatic change in the Church and the transformation of the Communist-time ‘ecclesia militans’ into an ‘ecclesia serviens’ rooted in a free society. The Church has to reconsider its mission and carry out a kind of ‘aggiornamento’. In this new situation, pastoration has to go through a reform as well. In post-Communist societies this transformation and pastoration could felicitously be called the ‘post-socialist imitation of Christ’. The situation in which the Polish Catholic Church has been living after the political change presumes the renewal process termed ‘new evangelisation’ by Pope John Paul II. With regard to the change in social order, the Church is facing the challenge of establishing a new working style of pastoration. In order to avoid the fragmentation of pastoral work into several individual concepts of spiritual counselling, it has to be closely linked to theology. This is why pastoration has turned to modern humanities and social sciences and has been involved in critical dialogue with these disciplines as part of the responsible counselling work of the Church. Pastoral theology in Poland has a lot to catch up within this respect. The atheist state thwarted all Church attempts to provide theological education to laypersons. In Communist times the Polish Catholic Church was allowed to run one university only (KUL), which was also the only Catholic university in the whole Eastern bloc. In the meantime, the theological landscape has been transformed. After the political change, the Church could take the opportunity to create better theological education for laymen as well. It succeeded in taking over one of the universities in Warsaw (UKSW) and founding several theological faculties that have also been recognised by the state. The weakness of present-day Polish theology is definitely the academic staff, 90 percent of which consists of ordained people also active in pastoral counselling. Professors are capable of covering the existing faculties and institutes but they usually fulfil duties in a number of institutions. Interdisciplinary cooperation has become possible in Poland, too; therefore, students of theology can choose from new specialisation courses such as ethics, journalism, social communication and family studies. The number of students in Church-run Polish universities is estimated to amount to 16,000. The fact that this number includes both candidates for priesthood and lay theologians seems to be extremely important with view of the future of the Church in Poland.